Amaryllis - Castle, Jayne (New York : Pocket Star Books, 1996)
Recently cut off from her home planet with the rest of her colony, psychic detective Amaryllis Lark is approached by Lucas Trent, the head of Lodestar Exploration, to help him expose a corporate thief.
Keywords: Life on other planets -- Fiction; Psychics -- Fiction; Women detectives -- Fiction; Romance fiction